Examining sexual functions of women before and after menopause in Turkey - Yağmur, Yurdagül (Afr Health Sci, 2019)
BACKGROUND: Sexuality is an important factor that completes the lives of individuals and affects people in all age groups. OBJECTIVES: To examine the sexual functions of women before and after menopause. METHODS: This cross-sectional study was conducted at the Family Health Centers in Tunceli Turkey,\ between September 2014 and February 2015. The study data were obtained using a Questionnaire and the Female Sexual Function Index. The data were analyzed by number, percentage distribution, mean, standard deviation, t-test, and using binary logistic regression analysis. RESULTS: The mean Female Sexual Function Index score of the women was 23.8±8.0. The Female Sexual Function Index score of 59.7% of women was below the cut-off score (26.55) and was accepted indicative of sexual dysfunction. Low educational level (P < 0.01), low income (P < 0.01), and menopausal status (P < 0.0001) of the women were risk factors for sexual dysfunction. CONCLUSION: Prevalence of sexual dysfunction in the women was very high and they indicated no effort to seek medical care. Low educational and income level and menopausal status of the women were three factors increasing the risk of sexual dysfunction. Awareness of the society and the healthcare professionals about the issue should be increased.